2016
DOI: 10.1108/jfbm-02-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Do family-managed and non-family-managed firms internationalize differently?

Abstract: Purpose Although the concepts of family business, internationalization, and agency theory have received some attention in the relevant literature, these concepts and theories have been used independently. The purpose of this paper is to help close the gap between what is known and what needs to be known about the decision-making processes of internationalization of family managers (FM) and non-family managers (NFMs). Design/methodology/approach The paper analyzes the story of Busscar, a Brazilian firm that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
6
23
0
Order By: Relevance
“…However, several studies specifically account for international scope, proposing more precise and robust theoretical mechanisms and delivering empirical results that diverge from those summarized earlier. For example, Alessandri, Cerrato, and Eddleston (2018) conclude that family involvement is associated with greater home region orientation, while Arregle et al (2017) and others (Avrichir, Meneses, & dos Santos, 2016;Bauweraerts & Vandernoot, 2019) specifically associate it with reduced scope of internationalization. In contrast, Zahra (2003) initially speculated, based on stewardship theory, that family involvement should have a positive effect on international scope, but this paper actually found that the effects of ownership and management differ: ownership exerted a positive effect on international scope, and management a negative one.…”
Section: Explaining Family Firms' International Scopementioning
confidence: 99%
“…However, several studies specifically account for international scope, proposing more precise and robust theoretical mechanisms and delivering empirical results that diverge from those summarized earlier. For example, Alessandri, Cerrato, and Eddleston (2018) conclude that family involvement is associated with greater home region orientation, while Arregle et al (2017) and others (Avrichir, Meneses, & dos Santos, 2016;Bauweraerts & Vandernoot, 2019) specifically associate it with reduced scope of internationalization. In contrast, Zahra (2003) initially speculated, based on stewardship theory, that family involvement should have a positive effect on international scope, but this paper actually found that the effects of ownership and management differ: ownership exerted a positive effect on international scope, and management a negative one.…”
Section: Explaining Family Firms' International Scopementioning
confidence: 99%
“…So far most research on family business focus on a wide range of dichotomies between family and nonfamily firms in their ownership, governance, returns, networks and relationships, leadership, careers and management styles (see Steward and Hitt, 2012; Avrichir et al , 2016; James et al , 2017). Although some studies addressed the decision-making topic in family firms, most have focused on very specific decisions, e.g., capital structure (Matthews et al , 1994), intergenerational successions (Bjuggren and Sund, 2001) or location preference (Kahn and Henderson, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, he also proposed the absence of professional business acumen can create disadvantages for an owner-managed firm that professionally managed companies would not meet. A further aspect of the agency relationship is that managers tend to use firm's resources more freely if the firm is not managed by the owner (Avrichir et al, 2016).…”
Section: Principal-agent Relationshipmentioning
confidence: 99%